1997
DOI: 10.1038/hdy.1997.46
|View full text |Cite
|
Sign up to set email alerts
|

Do island populations have less genetic variation than mainland populations?

Abstract: Island populations are much more prone to extinction than mainland populations. The reasons for this remain controversial. If inbreeding and loss of genetic variation are involved, then genetic variation must be lower on average in island than mainland populations. Published data on levels of genetic variation for allozymes, nuclear DNA markers, mitochondrial DNA, inversions and quantitative characters in island and mainland populations were analysed. A large and highly significant majority of island populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

67
617
12
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 862 publications
(707 citation statements)
references
References 126 publications
67
617
12
11
Order By: Relevance
“…Our results indicated that low genetic variation may also have been a contributor, as previously suggested (Simberloff 1988). It is also possible that some of this low genetic variation may reflect the smaller effective population size of island populations (Frankham 1997). Unfortunately, no known samples exist from mainland populations (Gross 1928).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that low genetic variation may also have been a contributor, as previously suggested (Simberloff 1988). It is also possible that some of this low genetic variation may reflect the smaller effective population size of island populations (Frankham 1997). Unfortunately, no known samples exist from mainland populations (Gross 1928).…”
Section: Discussionmentioning
confidence: 99%
“…Its range is becoming increasingly fragmented as a result of habitat loss and highway construction, causing the fragmented populations to become genetically isolated and increasing their risk of local extinction from random processes (VelĂĄzquez, 1993;Frankham, 1997). However, genetic variation in R. diazi is similar to that of more widespread and less fragmented genera of Mexican rabbits, such as Sylvilagus and Lepus (Cervantes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also reported correlations between surrogates of population size and genetic diversity, such as range size in plants, island area (both positive), rates of chromosomal evolution and body size (both negative) (see Frankham, 1996; Table 1). Further, average genetic diversity of island populations (presumed to have smaller N) is lower than that for mainland populations (Frankham, 1997).…”
Section: Correlations Of Genetic Diversity With Population Size and Fmentioning
confidence: 99%